2013
DOI: 10.3852/12-131
|View full text |Cite
|
Sign up to set email alerts
|

A new species and a new record of Diatrypaceae from Panama

Abstract: Based on opportunistic collections of fungi in Panama, two species of Diatrypaceae (Xylariales) are described and illustrated. One of them, Eutypella semicircularis, found twice on branches probably belonging to Alnus acuminata, is new to science. It differs from known species of Eutypella and Peroneutypa with strongly allantoid or semicircular ascospores, such as E. crustata and P. curvispora, in having larger ascospores that sometimes almost form a circle and broader stromata, among other differences. Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Although 251 species epithets of Eutypella have been listed in Index Fungorum ( 2021), the most of species are lacking DNA sequence. In phylogenetic analyses of Diatrypaceae, it showed that Eutypella was polyphyletic (Acero et al, 2004;Chacón et al, 2013;de Almeida et al, 2016;Shang et al, 2017). Thus, further studies of the taxa in Eutypella is needed.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 251 species epithets of Eutypella have been listed in Index Fungorum ( 2021), the most of species are lacking DNA sequence. In phylogenetic analyses of Diatrypaceae, it showed that Eutypella was polyphyletic (Acero et al, 2004;Chacón et al, 2013;de Almeida et al, 2016;Shang et al, 2017). Thus, further studies of the taxa in Eutypella is needed.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…The number of ascospores per ascus (eight spores vs. multiple spores) has been used traditionally to differentiate the genera of Diatrypaceae (Diatrype vs. Diatrypella and Cryptovalsa vs. Eutypella). However, the recent studies indicated that the polysporous ascus feature maybe not significant in Diatrypaceae (Acero et al, 2004;Trouillas et al, 2011;Chacón et al, 2013;Liu et al, 2015). A thorough revision is needed to resolve the problematic situation of Diatrypaceae, which includes a mass of misidentified genus/species, as a result of the unstable phylogenetic frame with type materials.…”
Section: Other Genera Included In Diatrypaceaementioning
confidence: 99%
“…Acero et al (2004) reported that Cryptosphaeria, Diatrype, Diatrypella, Eutypa and Eutypella based on ITS sequence data were polyphyletic and confused probably lacking of tub2 gene sequences or misidenti ed species. However, these ve genera are still polyphyletic within the family from previous studies (Trouillas et al 2011;Chacón et al 2013;de Almeida et al 2016;Shang et al 2017;Mehrabi et al 2019;Konta et al 2020;Dayarathne et al 2020a, b) based on the ITS and tub2 sequences data. In our study, the Diatrype and Diatrypella are not polyphyletic with the ve novel taxa and one novel combination constituting separate lineages ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Currently, 251 species epithets of Eutypella are listed in Index Fungorum (2020), but only a few species have sequence data. Phylogenetic analyses of Diatrypaceae from previous studies show that Eutypella is polyphyletic Chacón et al 2013;de Almeida et al 2016;Shang et al 2017). Therefore, further study of the taxa in this genus is needed.…”
Section: Taxonomymentioning
confidence: 99%
“…In the past, this family belonged to Diatrypales and in current classification Diatrypaceae belongs to Xylariales (Augusto et al 2016 ; Hyde et al 2020d ; Wijayawardene et al 2020 ). Diatrypaceous taxa are most likely colonise any kind of ecosystem with woody plants in both aquatic and terrestrial habitats and some are pathogens of economic crops as well as forest trees (Chacón et al 2013 ; Senanayake et al 2015 ; Dayarathne et al 2016 ; Hyde et al 2020d ; Konta et al 2020 ). There are 20 genera accounted to Diatrypaceae (Wijayawardene et al 2020 ).…”
Section: Taxonomymentioning
confidence: 99%